Progress in thermochemical conversion of aquatic weeds in shellfish aquaculture for biofuel generation: Technical and economic perspectives. (January 2022) - Azwar, Elfina; Wan Mahari, Wan Adibah; Rastegari, Hajar; Tabatabaei, Meisam; Peng, Wanxi; Tsang, Yiu Fai; Park, Young-Kwon; Chen, Wei-Hsin; Lam, Su Shiung
Graphical abstract: Highlights: Valorisation of aquatic weed in shellfish aquaculture is reviewed. Aquatic weeds have high content of lignocellulose, carbohydrate, protein, lipids. Thermochemical technologies are emerging for aquatic weeds conversion to biofuel. The key operating parameters of the thermochemical conversions are discussed. Techno-economic analysis of aquatic weed thermochemical conversion is reviewed. Abstract: Rapid growth of aquatic weeds in treatment pond poses undesirable challenge to shellfish aquaculture, requiring the farmers to dispose these weeds on a regular basis. This article reviews the potential and application of various aquatic weeds for generation of biofuels using recent thermochemical technologies (torrefaction, hydrothermal carbonization/liquefaction, pyrolysis, gasification). The influence of key operational parameters for optimising the aquatic weed conversion efficiency was discussed, including the advantages, drawbacks and techno-economic aspects of the thermochemical technologies, and their viability for large-scale application. Via extensive study in small and large scale operation, and the economic benefits derived, pyrolysis is identified as a promising thermochemical technology for aquatic weed conversion. The perspectives, challenges and future directions in thermochemical conversion of aquatic weeds to biofuels were also reviewed. This review provides useful information to promote circular economy by integrating shellfish aquaculture with thermochemical biorefinery of aquatic weeds rather than disposing them in landfills.